Penggunaan Global Positioning System dalam Tafsir Konstitusional Hak atas Informasi - Hwian Christianto (The Constitutional Court of the Republic of Indonesia, 2020)
Constitutional Court Decision Number 23/PUU-XVI/2018 has become the most waited decision by the society as the user of technology in driving, more specifically the use of Global Positioning System (GPS). There are at least 2 (two) main issues which are debated in the submission of the application of the constitutional testing of Article 106 paragraph (1) and Article 283 of Law 22/2009. First, the use of GPS is needed by the society so that it has become a part of the fulfillment of economical right. Second, the effort of protection of public order is being maintained by the former of Law 22/2009. A normative judicial method was used based on the legal principles, the ongoing regulations, and the consideration of the court on the legal issues being discussed. The court in the consideration gave a philosophical historical analysis on the existence of both rules of law as the base to understand the important meaning of the ban on the activity that causes distractions in driving on the street. Strangely, the court did not directly state that the use of GPS was definitely included in the second scope of both rules of law. The use of GPS needs to be case studied as an action that distracts concentration. Although the court finally stated that the application was denied, the decision gave a balanced understanding on the need of GPS as the navigation system while driving and the protection of the road users.